Microbial Degradation of Citric Acid in Low Level Radioactive Waste Disposal: Impact on Biomineralization Reactions - Byrd, Natalie; Lloyd, Jonathan R.; Small, Joe S.; Taylor, Frank; Bagshaw, Heath; Boothman, Christopher; Morris, Katherine (Frontiers in Microbiology, 2021)
Organic complexants in radioactive wastes and can challenge waste disposal as they may enhance mobility of radionuclides and contaminant species via chelation. The principal organic complexing agents in low level radioactive wastes (LLW) originate from chemical decontamination activities. Polycarboxylic decontaminants such as citric acid are of interest as currently there is a paucity of data on their biodegradation at high pH and under disposal conditions. This work explores the biogeochemical fate of citric acid, a model decontaminant, under high pH anaerobic conditions relevant to cementitious LLW disposal. Anaerobic microcosm experiments were set up, using a high pH adapted microbial inoculum from a well characterized environmental site, to explore biodegradation of citrate under representative repository conditions. Experiments were initiated at three different pH values (10, 11 and 12) and citrate was supplied as the electron donor and carbon source, under fermentative, nitrate-, Fe(III)- and sulfate- reducing conditions. Results showed that citrate was oxidized using nitrate or Fe(III) as the sole electron acceptor at > pH 11. Citrate was fully degraded and removed from solution in the nitrate reducing system at pH 10, and and partially at pH 11. Here, the microcosm pH decreased as protons were generated during citrate oxidation. In the Fe(III)-reducing systems, the citrate removal rate was slower than in the nitrate reducing systems. This was presumably as Fe(III)-reduction consumes fewer moles of citrate than nitrate reduction for the same molar concentrations of electron acceptor. The pH did not change significantly in the Fe(III)-reducing systems. Sulfate reduction only occurred in a single microcosm at pH 10. Here, citrate was fully removed from solution, alongside ingrowth of acetate and formate, likely fermentation products. The acetate and lactate were subsequently used as electron donors during sulfate-reduction and there was an associated decrease in solution pH. Interestingly, in the Fe(III) reducing experiments, Fe(II) ingrowth was observed at pH values recorded up to 11.7. Here, TEM analysis of the resultant solid Fe-phase indicated that nanocrystalline magnetite formed as an end product of Fe(III)-reduction under these extreme conditions. These results are important to improve long-term environmental safety case development for cementitious LLW waste disposal.